2014
DOI: 10.1186/1556-276x-9-251
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia gas sensors based on chemically reduced graphene oxide sheets self-assembled on Au electrodes

Abstract: We present a useful ammonia gas sensor based on chemically reduced graphene oxide (rGO) sheets by self-assembly technique to create conductive networks between parallel Au electrodes. Negative graphene oxide (GO) sheets with large sizes (>10 μm) can be easily electrostatically attracted onto positive Au electrodes modified with cysteamine hydrochloride in aqueous solution. The assembled GO sheets on Au electrodes can be directly reduced into rGO sheets by hydrazine or pyrrole vapor and consequently provide the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 50 publications
3
50
0
Order By: Relevance
“…According to Wang et al [9] revelation that in an air environment, oxygen molecules absorbed onto the surface of ZnO films to form O 2− , O − , O − 2 ions depending on the temperature by extracting electrons from the conduction band. This phenomenon would result in the formation of a depletion region at the surface.…”
Section: The Sensing Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Wang et al [9] revelation that in an air environment, oxygen molecules absorbed onto the surface of ZnO films to form O 2− , O − , O − 2 ions depending on the temperature by extracting electrons from the conduction band. This phenomenon would result in the formation of a depletion region at the surface.…”
Section: The Sensing Mechanismmentioning
confidence: 99%
“…Detection of NH 3 in trace amounts is important in terms of environmental protection and human health, as well as industry production. In recent years, numerous materials including semiconducting oxide materials, such as ZnO [1,2], ZrO 2 [3], CdO [4] and TiO 2 [5], organic compounds [6,7] and novel materials such as carbon nanotubes [8] and graphene [9,10] are exploited for ammonia detection due to their superior ammonia gas sensing properties. Composite system based sensors have been demonstrated good sensitivity and selectivity to a particular gas [11,12] by varying the type and composition of the components of the composite such as metal oxide-metal oxide [1,13], novel materials (carbon nanotube and graphene)-metal oxide [9,14], polymer-metal oxide [8,15] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Patois et al [12] have studied ammonia gas sensing properties on microelectrode arrays of electrochemically deposited polypyrrole films. Ammonia gas sensing studies are also reported on rGO sensing devices, fabricated by self-assembled technique [13]. Graphenepolypyrrole composites prepared by oxidative polymerization technique are used for supercapacitor and Hg 2+ removal applications, respectively [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A few-layered reduced graphene oxide (rGO) has recently been proposed as a promising gas sensing element owing to its controllable surface defect density. However, pristine rGO-based gas sensors exhibited relatively low sensitivity [13] or long recovery time [14,15], or required a complicated fabrication process [16].…”
Section: Introductionmentioning
confidence: 99%